2021
DOI: 10.3389/feduc.2021.666087
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Higher Education: A Bibliometric Review Study

Abstract: For more than three decades, higher education has attracted growing interest from scholars, students, and academic institutions worldwide. This paper aims to analyze the literature review of quality of higher education, using the bibliometric analysis adapted from VOSviewer software to examine the data of 500 studies published in the Web of Science from 2000 to 2018 related to this topic. The results were presented and discussed with the following approaches: keywords, authors, references (research papers), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 24 publications
1
33
0
8
Order By: Relevance
“…The findings of this study will assist interested academics and educational policymakers (Brika et al, 2021) in the field of e-learning in understanding the current state of e-learning and identifying the different research trends in light of COVID-19. Additionally, it will serve as the beginning point for new research during the COVID-19 crisis, which will examine various problems and trends.…”
Section: Discussionmentioning
confidence: 96%
“…The findings of this study will assist interested academics and educational policymakers (Brika et al, 2021) in the field of e-learning in understanding the current state of e-learning and identifying the different research trends in light of COVID-19. Additionally, it will serve as the beginning point for new research during the COVID-19 crisis, which will examine various problems and trends.…”
Section: Discussionmentioning
confidence: 96%
“…These authors also emerged in another bibliometric review studies. To illustrate, Brika et al (2021) found that A. Parasuraman, L. Harvey, and B. Stansaker were the most cited authors in the studies focusing on quality in higher education. When the most-cited and co-cited documents were examined, the common scope of the topics appeared as management, sustainability, and change.…”
Section: Discussionmentioning
confidence: 99%
“…According (Lotka, 1926) The term "bibliometric analysis" refers to a "method for measuring researcher productivity" (Brika et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, bibliometric research enables participants to participate in a variety of tasks, thereby minimizing bias and research choices (Mulet-Forteza et al, 2019). The research preparation was carried out in numerous stages that followed the research utilizing the bibliometric approach that had previously been carried out (Brika et al, 2021;Cao et al, 2021;Khanra et al, 2021).…”
Section: Methodsmentioning
confidence: 99%